DEVELOPMENT OF IRIS RECOGNITION SYSTEM - Mohd Kamarudin, Nur Eliza (Universiti Teknologi PETRONAS, 2016)
This project implements an iris recognition algorithm as a biometric identification. There is a need for reliable and security identification since typical identification methods using identity cards, passwords, and user name possess threats to the security of an organization because of human error. Iris is the best part of human body for biometric recognition compared to other biometric features like fingerprint, face, and veins. Uniqueness of iris is proven can increase the security and efficiency of recognition system. The “objective of this” project “is to develop” a secure “iris recognition” algorithm for identification management and access control. Iris recognition in this project consist of segmentation, iris normalization, feature extraction, and lastly template matching. Hough transform method is used in iris segmentation to detect location of iris and pupil region in the image. Segmented iris region is then normalized to a constant size of rectangular block.